2014
DOI: 10.1002/2013gc005194
|View full text |Cite
|
Sign up to set email alerts
|

In situ geochemistry of Lower Paleozoic dolomites in the northwestern Tarim basin: Implications for the nature, origin, and evolution of diagenetic fluids

Abstract: Lower Paleozoic sedimentary rocks in the northwestern Tarim basin were strongly altered by complicated geofluids, which resulted in the occurrence of various diagenetic minerals (e.g., dolomite). Here, in situ major, trace, and rare earth element geochemistry of Lower Ordovician diagenetic dolomite grains as well as petrography were performed to unravel the geochemical features, the nature, and origin of the diagenetic fluids. The results indicate that different geochemical information can be detected within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 109 publications
1
49
0
Order By: Relevance
“…; Zhang et al . ). Hence, it is possible that the late‐stage diagenetic minerals in this study are hydrothermal in origin or are closely related to the hydrothermal activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Zhang et al . ). Hence, it is possible that the late‐stage diagenetic minerals in this study are hydrothermal in origin or are closely related to the hydrothermal activity.…”
Section: Discussionmentioning
confidence: 99%
“…; Zhang et al . ). In contrast, carbonate reservoirs away from granite intrusions and diabase dikes have relatively high porosity (locally >10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(d) Binary diagram of UCC normalized values showing Ce/Ce* and Pr/Pr* relationship after Bau and Dulski () and Zhang et al. (). Field a: neither Ce nor La anomaly; Field b: positive La anomaly, no Ce anomaly; Field c: negative La anomaly, no Ce anomaly; Field d: true positive Ce anomaly; Field e: true negative Ce anomaly.…”
Section: Resultsmentioning
confidence: 99%
“…() demonstrated that even 2% contamination by shale can obliterate diagenetic elemental anomalies and result in relatively flat REE patterns. Due to the high REE concentration of shales and clays, a positive correlation between these incompatible elements and ∑REE should be present if contamination has occurred (Bolhar, Kamber, Moorbath, Fedo, & Whitehouse, ; Frimmel, ; Zhang et al., ). Thorium values for dolomite range between 0.02 and 1.14 p.p.m., and Al values range from 87 to 6220 p.p.m.…”
Section: Interpretation and Discussionmentioning
confidence: 99%